Evaluation of the effect of natural peptide 'Urocortin' on corticotrophin releasing factor (CRF) receptor expression in ND7/23 cells - Omair Anwar Mohiuddin; Chris Biggs (Brazilian Journal of Pharmaceutical Sciences, 2015)
CRF receptors are involved in the stress management of the cells and are believed to have a cytoprotective role in the body. CRF receptors have been reported to be potential drug targets for the treatment of neurodegenerative disorders. The cell line used in the study is ND7/23 (mouse neuroblastoma and rat dorsal root ganglion neuron hybridoma). The aim of the study was to confirm the expression of CRF receptors in ND7/23 cells and to determine if urocortin (Ucn) can enhance the expression of CRF receptors. ND7/23 cells were cultured in RPMI 1640 media and cells grown after the second passage were used for the experiments. RNA was extracted from the cells and amplified by RT-PCR to confirm the presence of CRF receptors. The cells were then subjected to oxidative stress by hydrogen peroxide (0.00375%) and divided into two groups i.e. control and Ucn (10-8 μM) treated. Later RNA was extracted from both group of cells and PCR was performed. Finally, densitometry analysis was conducted on the agarose gel to determine the quantity of PCR product formed. PCR experiment confirmed the expression of both CRF-R1 and CRF-R2 in the cell line, but CRF-R1 was found to be expressed more strongly. Densitometry analysis of the PCR product and calculation of the relative expression of CRF receptors indicated a higher level of expression of CRF receptors in samples treated with Ucn as compared to those that were kept untreated. The results indicate that Ucn may be useful for the management of neuro-degenerative disorders and further studies may be carried out to establish its use as a therapeutic agent.